Treatment of Kidney Stones Using Diosgenin - Mitra, Reema; Kumar, Munish (International Journal of Psychosocial Rehabilitation, 2019)
Kidney stone is a common disease in the world. These stones are present in solid structures which lead to severe pain and discomfort in kidney. This problem is also known as urolithiasis which affects approximately 12 percent of the world's population. Kidney stone is the third most prevalent disease among the various diseases which are affecting the urinary system. The accumulation of crystals / stones, usually made of calcium oxalate, characterizes this disease. Having the stones repeated after treatment is the main challenge. In males there is a 78- 81% and in females a 47-60% rate of recurrence. In contrast to women, the occurrence of stones is three times higher in men. Though some products are available on the market, most of them do not deal with reoccurrence problems. Our researches have shown the promising role of diosgenin in stone prevention, so it may address the reoccurrence problem. It is also a drug derived from plants and not artificial, and therefore may have fewer side effects. In this paper, treatment of kidney has been performed with the utilization of diosgenin.